2014
DOI: 10.1159/000356023
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Consequences of Childhood Obesity

Abstract: The severity and frequency of childhood obesity has increased significantly over the past three to four decades. The health effects of increased body mass index as a child may significantly impact obese youth as they age. However, many of the long-term outcomes of childhood obesity have yet to be studied. This article examines the currently available longitudinal data evaluating the effects of childhood obesity on adult outcomes. Consequences of obesity include an increased risk of developing the metabolic syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
286
1
23

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(311 citation statements)
references
References 40 publications
1
286
1
23
Order By: Relevance
“…Total adiponectin and multimeric high-molecubolic syndrome, cardiovascular disease, type 2 diabetes, obstructive sleep apnea, and polycystic ovarian syndrome 4) . Obesity increases lipid peroxidation and induces persistent platelet activation, affecting the vascular endothelial function and probably conferring premature atherogenicity 5) .…”
Section: Haemostatic Biomarkersmentioning
confidence: 99%
“…Total adiponectin and multimeric high-molecubolic syndrome, cardiovascular disease, type 2 diabetes, obstructive sleep apnea, and polycystic ovarian syndrome 4) . Obesity increases lipid peroxidation and induces persistent platelet activation, affecting the vascular endothelial function and probably conferring premature atherogenicity 5) .…”
Section: Haemostatic Biomarkersmentioning
confidence: 99%
“…These last parameters, according to the most recent literature data [6][7][8], allow a more reliable quantification and stratification of both cardiovascular risk and metabolic syndrome [9][10][11][12]. Because it is internationally admitted that cut-offs must be specific for each population [13], a waist-height ratio cut-off equal to or higher than 0.50 for overweight children and 0.60 for obese children [14,15] was decided, in agreement with the literature specific for the Italian population. Yet, the waist/height ratio assessment was narrowed to the 5-6 and 8-9 age ranges, as we found that this measurement was not connected with the BMI in the 3-4 age range children [16].…”
Section: Methodsmentioning
confidence: 81%
“…[2] Among the NCDs risk factors, obesity needs particular attention, since metabolic syndrome and diabetes are directly associated with obesity. [3,4] Early childhood obesity is associated with a higher risk of developing NCDs at a younger age and premature death in adulthood, [5,6] since adiposity tracks into adulthood. [7] Prevention of childhood obesity is a key approach to the primary prevention of noncommunicable diseases.…”
Section: Introductionmentioning
confidence: 99%